Analisis Studi Kasus Sengketa Lahan Warga Tanah Merah Dengan Depo Pertamina Plumpang - Lulu Aisha Fakhirah; Noel Christian; Reyna Zahia; Muhammad Aryo Dwinanda Mukti; Muhammad Artferyo; Nadhifa Putri Eriana; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The functions and benefits of land are very important for human life, this can be seen from the many land disputes that have long been a social reality in every society, although in different forms and identities. One example is the Tanah Merah Dispute. This study uses a normative approach with data analysis using a qualitative model. The results of the study show that the Tanah Merah land is owned by several parties, namely the people, Pertamina and the private sector. The solution to the Tanah Merah dispute is to relocate the Pertamina Plumpang Depot to the relocation of local residents. In general, the settlement of disputes in society can be classified into two ways, namely through the court (litigation) and outside the court (non-litigation). Out of court dispute resolution that is often carried out by the community includes involving two or more interested parties (negotiation), a dispute resolution process in which the disputing parties utilize the help of an independent third party as a mediator (mediator) and involves more than two parties whose job is to assist the other party. litigants by seeking a solution together (facilitation).Â